FARMERS’ CHOICE OF POSTHARVEST MANAGEMENT PRACTICES: DETERMINANTS AND FOOD SECURITY IMPLICATIONS IN THE TOLON DISTRICT OF GHANA - Samira Adam Abubakar; Hamdiyah Alhassan; Dagunga, Gilbert (UDS International Journal of Development, 2023)
Postharvest losses remain a key threat to the efforts by developing countries to achieving the zero hunger global agenda. Farmers in many areas have employed mechanisms aimed at managing postharvest losses. This study, therefore, sought to analyze rice farmers' choice of postharvest management practices and its implication on household food security in Tolon district, Ghana. The results revealed that, the various postharvest management practices among rice farmers were chemical application, heat control method, and cleaning and sorting method. Estimation results from the multivariate probit model indicated that, FBO membership, household size, access to credits, farm size and farmer awareness of postharvest loss influence farmers’ choice of postharvest management practices. Likewise, the ordered probit results showed that farmers who employ heat control in managing postharvest losses were more likely to be at the acceptable level of food consumption. The effect of heat control was found to be more effective when combined with other postharvest management practices like chemical control and cleaning/sorting. The outcome of the study suggests the need to encourage the use of heat control postharvest management strategies which may go a long way to help in the achievement of the zero-hunger global agenda. This should be used in combination with chemical control and cleaning/sorting. Keywords: Rice farmers, Postharvest losses, Food Security, Multivariate Probit, Ordered Probit model